Development and preliminary validation of an integrated efficacy–tolerability composite measure for the evaluation of analgesics. Issue 7 (July 2015) - Katz, Nathaniel P.; Mou, Joy; Trudeau, Jeremiah; Xiang, Jim; Vorsanger, Gary; Orman, Camille; Kim, Myoung
Abstract : Abstract: The goal of this analysis was to develop and evaluate integrated measures of benefit and tolerability of analgesic drugs in clinical trials. We evaluated an efficacy–tolerability composite (ETC) measure combining different cutoff values for daily pain reduction (≥20%, ≥30%, or ≥50% pain reduction) and adverse events (AEs) (no AE, no or mild AEs, no or mild drug-related AEs). Nine ETC cutoff values (3 × 3) were tested using data from a randomized double-blind trial comparing tapentadol extended release (ER) (n = 310), oxycodone controlled release (CR) (n = 322), and placebo (n = 314) in subjects with chronic low back pain. Efficacy–tolerability composite scores were calculated as the mean number of days a subject met the ETC criterion divided by the number of days the subject was expected to be in study; ETC scores were then averaged in each treatment group. For all 9 ETC measures, validity was demonstrated by significant correlation of ETC scores with patients' Global Impression of change and with change from baseline in pain scores. Tapentadol ER ETC scores were statistically significantly higher than oxycodone CR ETC scores for 4 of the ETC measures. "No/mild drug-related AE and ≥20% pain reduction" demonstrated the best overall validity (correlation with patients' global impression of change) and responsiveness (discrimination between treatment groups), yielding a higher standardized effect size for tapentadol ER compared with placebo (0.19 [95% confidence interval: 0.031–0.346]) and with oxycodone CR (0.23 [95% confidence interval: 0.070–0.383]) than other cutoff values. Thus, we have identified herein a composite measure that seems to be a valid and responsive measure of the overall efficacy and tolerability of analgesics in clinical trials. Abstract : We have identified a composite measure of the overall efficacy and tolerability of analgesics in clinical trials, which seems valid and responsive.